Exposure to legacy and emerging phthalates and bisphenols in recycling workers: Evidence from the GreenMetalWaste study - Neža Palir; Eva Dock; Malin Engfeldt; Maria Albin; Else Åkerberg Krook; Marie Bengtsson; Anna Dahlman Höglund; Robert Linder; Lars Modig; Christian Lindh; Anja Stajnko; Karin Broberg (Environmental Research, 2026)

Metal and dust exposure in workers from the metal recycling industry in Sweden: cross-sectional GreenMetalWaste study - Anja Stajnko; Michael Levi; Malin Engfeldt; Robert Linder; Mats Leeman; Else Åkerberg Krook; Eva Assarsson; Henrik Enquist; Camilla Dahlqvist; Åsa Ek; Karin Lovén; Theo Bodin; et al. (International Journal of Hygiene and Environmental Health, 2026)

Occupational exposure to chemicals and particles and incidence of myocardial infarction—a nationwide cohort study in Sweden - Karin Grahn; Claudia Lissåker; Tomas Andersson; Per Gustavsson; Håkan Tinnerberg; Pernilla Wiebert; Lars Alfredsson; Karin Broberg; Maria Albin; Jenny Selander (Environmental Research, 2025)

Risk of preeclampsia and gestational diabetes after occupational exposure to chemicals during pregnancy–A cohort study of births in Sweden 1994–2014 - Per Gustavsson; Claudia Lissåker; Maria Albin; Lars Alfredsson; Pernilla Wiebert; Håkan Tinnerberg; Karin Grahn; Lars Rylander; Jenny Selander (Environmental Research, 2025)

The SAM-Krom biomonitoring study shows occupational exposure to hexavalent chromium and increased genotoxicity in Denmark - Anne Thoustrup Saber; Marcus Levin; Pete Kines; Kukka Aimonen; Lucas Givelet; Christina Andersen; Anja Julie Huusom; Tanja Carøe; Niels Erik Ebbehøj; Frans Møller Christensen; Zheshun Jiang; Thomas Lundh; et al. (International Journal of Hygiene and Environmental Health, 2025)

Longitudinal changes in cardiovascular disease–related proteins in welders - Ulrike Maria Dauter; Anda Roxana Gliga; Maria Albin; Karin Broberg (International Archives of Occupational and Environmental Health, 2024)
Objective Occupational exposure to welding fumes is linked to a higher risk of cardiovascular disease; however, the threshold exposure level is unknown. Here, we aimed to identify changes in proteins associated with cardiovascular disease in relation to exposure to welding fumes. Methods Data were obtained from two timepoints six years apart for 338 non-smoking men (171 welders, 167 controls); of these, 174 (78 welders, 96 controls) had measurements available at both timepoints. Exposure was measured as personal respirable dust (adjusted for personal protective equipment), welding years, and cumulative exposure. Proximity extension assays were used to measure a panel of 92 proteins involved in cardiovascular processes in serum samples. Linear mixed models were used for longitudinal analysis. The biological functions and diseases related to the identified proteins were explored using the Ingenuity Pathway Analysis software. Results At both timepoints, the median respirable dust exposure was 0.7 mg/m 3 for the welders. Seven proteins were differentially abundant between the welders and controls and increased incrementally with respirable dust: FGF23, CEACAM8, CD40L, PGF, CXCL1, CD84, and HO1. CD84 was significant after adjusting for multiple comparisons. These proteins have been linked to disorders of blood pressure, damage related to clogged blood vessels, and chronic inflammatory disorders. Conclusion Exposure to mild steel welding fumes below current occupational exposure limits for respirable particles and welding fumes in Europe and the US (1–5 mg/m 3 ) was associated with changes in the abundance of proteins related to cardiovascular disease. Further research should evaluate the utility of these proteins as prospective biomarkers of occupational cardiovascular disease.

Hexavalent chromium still a concern in Sweden – Evidence from a cross-sectional study within the SafeChrom project - Zheshun Jiang; Linda Schenk; Eva Assarsson; Maria Albin; Helen Bertilsson; Eva Dock; Jessika Hagberg; Lovisa E. Karlsson; Pete Kines; Annette M. Krais; Stefan Ljunggren; Thomas Lundh; et al. (International Journal of Hygiene and Environmental Health, 2024)

Job demands and job control and their associations with disability pension—a register-based cohort study of middle-aged and older Swedish workers - Daniel Falkstedt; Melody Almroth; Tomas Hemmingsson; Angelo d’Errico; Maria Albin; Theo Bodin; Jenny Selander; Per Gustavsson; Katarina Kjellberg (International Archives of Occupational and Environmental Health, 2023)
Objectives Job demands and control at work and their combination, job strain, have been studied in relation to risk of disability pension (DP) previously. In the present study, based on registry data, we aimed to deepen the knowledge by analyzing major disease groups among the DPs, dose–response shape of the associations, and potential confounding effects of physical workload. Methods Approximately 1.8 million workers aged 44 or older and living in Sweden in 2005 were followed up for 16 years, up to a maximum of 65 years of age. We linked mean values of job demands and job control, estimated in a job-exposure matrice (JEM) by gender, to individuals through their occupational titles in 2005. These values were categorized by rank order, and, for the construction of job-strain quadrants, we used a median cut-off. Associations with DP were estimated in Cox proportional-hazards models. Results In models accounting for covariates including physical workload, low levels of job control were associated with higher risk of DP among both men and women. This association was most clear for DP with a psychiatric diagnosis, although a dose–response shape was found only among the men. High levels of job demands were associated with decreased risk of DP across diagnoses among men, but the same association varied from weak to non-existing among women. The high- and passive job-strain quadrants both showed increased risk of DP with a psychiatric diagnosis. Conclusion The results suggest that, at the occupational level, low job control, but not high job demands, contributes to an increased incidence of DP, particularly regarding DP with a psychiatric diagnosis.

Long-term exposure to traffic noise and risk of incident colon cancer: A pooled study of eleven Nordic cohorts - Nina Roswall; Jesse D. Thacher; Mikael Ögren; Andrei Pyko; Agneta Åkesson; Anna Oudin; Anne Tjønneland; Annika Rosengren; Aslak H. Poulsen; Charlotta Eriksson; David Segersson; Debora Rizzuto; et al. (Environmental Research, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Disability pensions related to heavy physical workload: a cohort study of middle-aged and older workers in Sweden - Daniel Falkstedt; Tomas Hemmingsson; Maria Albin; Theo Bodin; Anders Ahlbom; Jenny Selander; Per Gustavsson; Tomas Andersson; Melody Almroth; Katarina Kjellberg (International Archives of Occupational and Environmental Health, 2021)
Objectives The aim of the study was to examine the associations between heavy physical workload among middle-aged and older workers and disability pension due to any diagnosis, as well as musculoskeletal, psychiatric, cardiovascular or respiratory diagnoses. The population-based design made it possible to examine dose–response and potential gender differences in the associations. Methods About 1.8 million men and women aged 44–63 years and registered as living in Sweden in 2005 were followed regarding disability pension during 2006–2016, until ages 55–65 years. Mean values of physical workload and job control, estimated through gender-specific job-exposure matrices (JEMs), were assigned to individuals through their occupational titles in 2005. Exposure values were ranked separately for women and men and divided into quintiles. Associations were analyzed with Cox proportional-hazards regression. Results The analyses showed robust, dose–response associations between physical workload and disability pension with a musculoskeletal diagnosis in both genders: the adjusted hazard ratio and 95% confidence interval for those with the heaviest exposure was 2.58 (2.37–2.81) in women and 3.34 (2.83–3.94) in men. Dose–response associations were also seen in relation to disability pension with a cardiovascular or a respiratory diagnosis, though the hazard ratios were smaller. Physical workload was not associated with disability pension with a psychiatric diagnosis after adjustment for job control. Conclusion This study of the entire Swedish population of middle-aged and older workers suggests that higher degrees of physical workload may increase the risk of disability pension overall, and specifically with musculoskeletal, cardiovascular or respiratory diagnosis, in both women and men.

Investigating the risk of breast cancer among women exposed to chemicals: a nested case–control study using improved exposure estimates - Cecilia Videnros; Jenny Selander; Pernilla Wiebert; Maria Albin; Nils Plato; Signe Borgquist; Jonas Manjer; Per Gustavsson (International Archives of Occupational and Environmental Health, 2020)
Purpose The aim of this study was to examine if exposures to chemicals at the workplace were associated with an increased risk of postmenopausal breast cancer, using improved exposure estimates. Methods The design is a case–control study, nested within a cohort of women from the Malmö Diet and Cancer Study. The study comprised 2400 women, 731 cases and 1669 matched controls, born 1923–1950 and living in Malmö, Sweden between 1991 and 1996. An occupational hygienist reclassified the probability for exposure given by a job-exposure matrix, using individual data on work tasks. First-time diagnoses of invasive breast cancer were identified through the Swedish Cancer Registry. Results Women exposed to chemicals in their occupational environment had a statistically significantly increased risk (OR 1.59, 95% CI 1.11–2.29) of breast cancer, and the risk correlated positively with duration of exposure but not with exposure intensity. Women exposed to chlorinated hydrocarbon solvents for more than 10 years had a significant higher risk of breast cancer (OR 3.06, 95% CI 1.18–7.96) as well as women exposed to oil mist for more than 10 years (OR 3.08, 95% CI 1.12–8.49). Conclusions This study gives some support to the hypothesis that exposure to organic solvents as well as oil mist is associated with increased risk of breast cancer.

Mild steel welding is associated with alterations in circulating levels of cancer-related proteins - Anda R. Gliga; Tahir Taj; Maria Hedmer; Eva Assarsson; Lars Rylander; Maria Albin; Karin Broberg (Archives of Toxicology, 2019)
Welding fumes were recently classified as carcinogenic to humans and worldwide millions work as welders or perform welding operations. The purpose of this study was to identify new biomarkers of welding-induced carcinogenesis. We evaluated a panel of 91 putative cancer-related proteins in serum in a cohort of welders working with mild steel ( n = 77) and controls ( n = 94) from southern Sweden sampled on two occasions 6-year apart using a longitudinal analysis (linear mixed models). The significant results from the longitudinal analysis were tested for reproducibility in welders ( n = 88) and controls ( n = 69) sampled once during the same sampling period as timepoint 1 or timepoint 2 (linear regression models), i.e., in a cross-sectional setting. The models were adjusted for age, body-mass index, and use of snus. All study participants were non-smokers at recruitment. Exposure to welding fumes was assessed using questionnaires and respirable dust measurement in the breathing zone that was adjusted for personal respiratory protection equipment. The median respirable dust in welders was 0.7 (0.2–4.2) and 0.5 (0.1–1.9) mg/m 3 at the first and second timepoints, respectively. We identified 14 cancer-related proteins that were differentially expressed in welders versus controls in the longitudinal analysis, out of which three were also differentially expressed in the cross-sectional analysis (cross-sectional group). Namely, syndecan 1 (SDC1), folate receptor 1 (FOLR1), and secreted protein acidic and cysteine rich (SPARC) were downregulated, in welders compared with controls. In addition, FOLR1 was negatively associated with years welding. Disease and function analysis indicated that the top proteins are related to lung cancer as well as cell invasion and migration. Our study indicates that moderate exposure to welding fumes is associated with changes in circulating levels of putative cancer-related proteins, out of which FOLR1 showed a clear dose–response relationship. It is, however, unclear to which extent these changes are adaptive or potential early biomarkers of cancer.

Road traffic noise, air pollution and myocardial infarction: a prospective cohort study - Theo Bodin; Jonas Björk; Kristoffer Mattisson; Matteo Bottai; Ralf Rittner; Per Gustavsson; Kristina Jakobsson; Per-Olof Östergren; Maria Albin (International Archives of Occupational and Environmental Health, 2016)

New results on ground deformation in the Upper Silesian Coal Basin (southern Poland) obtained during the DORIS Project (EU-FP 7) - Marek Graniczny; Davide Colombo; Zbigniew Kowalski; Maria Przyłucka; Albin Zdanowski (Pure and Applied Geophysics, 2015)

Work stress, worries, and pain interact synergistically with modelled traffic noise on cross-sectional associations with self-reported sleep problems - Jesper Kristiansen; Roger Persson; Jonas Björk; Maria Albin; Kristina Jakobsson; Per-Olof Östergren; Jonas Ardö (International Archives of Occupational and Environmental Health, 2011)

Persulphate challenge in female hairdressers with nasal hyperreactivity suggests immune cell, but no IgE reaction - Kerstin Kronholm Diab; Lennart Truedsson; Maria Albin; Jørn Nielsen (International Archives of Occupational and Environmental Health, 2009)

Validation of urinary excretion of cyclophosphamide as a biomarker of exposure by studying its renal clearance at high and low plasma concentrations in cancer patients - Maria Hedmer; Peter Höglund; Eva Cavallin-Ståhl; Maria Albin; Bo A. G. Jönsson (International Archives of Occupational and Environmental Health, 2007)

Trait anxiety and modeled exposure as determinants of self-reported annoyance to sound, air pollution and other environmental factors in the home - Roger Persson; Jonas Björk; Jonas Ardö; Maria Albin; Kristina Jakobsson (International Archives of Occupational and Environmental Health, 2007)